Low Temperature Calorimetry Coupled with Molecular Simulations for an In-Depth Characterization of the Guest-Dependent Compliant Behavior of MOFs - Iacomi, Paul; Zheng, Bin; Krause, Simon; Kaskel, Stefan; Maurin, Guillaume; Llewellyn, Philip L. (Chemistry of Materials, 2020)
In this study adsorption microcalorimetry is employed to monitor the adsorption of four probes (argon, oxygen, nitrogen, and carbon monoxide) on a highly flexible mesoporous metal-organic framework (DUT-49, DUT = Dresden University of Technology), precisely measuring the differential enthalpy of adsorption alongside high-resolution isotherms. This experimental approach combined with force field Monte Carlo simulations reveals distinct pore filling adsorption behaviors for the selected probes, with argon and oxygen showing abrupt adsorption in the open pore form of DUT-49, in contrast with the gradual filling for nitrogen and carbon monoxide. A complex structural transition behavior of DUT-49 observed upon nitrogen adsorption is elucidated through an isotherm deconvolution in order to quantify the fractions of the open pore, contracted pore, and intermediate pore forms that coexist at a given gas pressure. Finally, the heat flow measured during the guest-induced structural contraction of DUT-49 allowed an exploration of complex open-contracted pore transition energetics, leading to a first assessment of the energy required to induce this spectacular structural change.
CRIS-Team Scopus Importer:2022-04-14